2021
DOI: 10.2217/lmt-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenopathy and Granulomas: Benignancy of Malignancy and Differential Diagnosis with Endobronchial Ultrasound-Transbronchial Needle Biopsy 19G Needle Fine-Needle Aspiration Biopsy

Abstract: Endobronchial ultrasound (EBUS) is a very useful tool for the diagnosis of lymphadenopathy of the mediastinum. Nowadays, EBUS can substitute video-assisted thoracic surgery when a 19G needle is used. Several studies have provided data for efficient diagnosis not only for lung cancer, but for also sarcoidosis, tuberculosis and lymphoma. We present five cases of EBUS-transbronchial needle biopsy 19G needle used for the diagnosis of mediastinum lymphadenopathy. We present not only the pathological diagnosis, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been previously presented that indifferent of the needle size the sample is enough for diagnosis and molecular next generation sequencing (NGS) investigation for lung cancer and other metastatic cancers in the lung parenchyma 5 , 15 , 18 . In a recent study it was observed that the 19G needle when compared to 22G needle has a larger sample size and it has a higher diagnostic sensitivity for lymphoma 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously presented that indifferent of the needle size the sample is enough for diagnosis and molecular next generation sequencing (NGS) investigation for lung cancer and other metastatic cancers in the lung parenchyma 5 , 15 , 18 . In a recent study it was observed that the 19G needle when compared to 22G needle has a larger sample size and it has a higher diagnostic sensitivity for lymphoma 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of endobronchial lung cancer cryo biopsies have been extensively used 14 . However; in the case of lymphadenopathy until now we have been using 22G, 21G and 19G needles as a minimal invasive technique compared to mediastinoscopy 15 . An effort has been made to acquire more sample and therefore the cryo probe 1.1mm has been used with an ERBE CRYO 2 system 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%